Marketing Regulated Products to a New Market: A Case Study - Ameen Talib; Yi Xin Ang (Indonesian Journal of Multidisciplinary Science, 2023)
The introduction of new products in a market would normally require an extensive marketing and promotion campaign. However, certain products are ‘regulated’ as they are deemed undesirable for society. Tobacco products are one such example. The regulation governing tobacco products does not allow for any marketing and promotion.  Shisha is a different form of tobacco consumption. Therefore, the introduction of Shisha in the Singapore market is introducing a new regulated product. This paper discusses a case study of the introduction and promotion of Shisha in Singapore. The study used qualitative approach with case study design. The data were generated from the researcher’s observation of a Shisha café in Singapore. The researcher made a field note as his data source and analyzed it by studying it and reduce them to only necessary ones. The case of the café is case that people can learn from in how to do personal based promotion and WOM. The strategy actually worked very well that the success of Shisha popularity eventually led to the banning of Shisha.